Plant growth‐promoting rhizobacteria isolation from rhizosphere of submerged macrophytes and their growth‐promoting effect on Vallisneria natans under high sediment organic matter load. Issue 2 (28th January 2021) - Wang, Chuan; Wang, Huihui; Li, Yahua; Li, Qianzheng; Yan, Wenhao; Zhang, Yi; Wu, Zhenbin; Zhou, Qiaohong
Summary: Sediment organic matter is a key stressor for submerged macrophyte growth, which negatively impacts the ecological restoration of lakes. Plant growth‐promoting rhizobacteria (PGPR) were screened from the rhizosphere of submerged macrophytes and used due to their promoting effect on Vallisneria natans under a high sediment organic matter load. Root exudates were used as the sole carbon source to obtain the root affinity strains. Eight isolates were selected from the 61 isolated strains, based on the P solubilization, IAA production, cytokinins production and ACC deaminase activity. The analysis of the 16S rDNA indicated that one strain was Staphylococcus sp., while the other seven bacterial strains were Bacillus sp. They were all listed in low‐risk groups for safety use in agricultural practices. The plant height significantly increased after inoculation with PGPR strains, with the highest rate of increase reaching 96%. This study provides an innovative technique for recovering submerged macrophytes under sediment organic matter stress. Abstract : Plant growth‐promoting rhizobacteria (PGPR) were screened from the rhizosphere of submerged macrophytes and selected by their plant growth promoting indicators. Inoculating with the excellent strains significantly promoted the growth of Vallisneria natans seedings under a high sediment organic matter load, which provides an innovative technique for recovering submerged macrophytes under sediment organic matter stress.